Polymodal Activation and Desensitization of TRPV1 Receptor in Human Odontoblasts-Like Cells with Eugenol - Karen L. Latorre; Paula A. Baldion (International Journal of Dentistry)
Dentinal hypersensitivity is a frequent reason for dental consultation, and its pathophysiology has not been fully clarified. Previous findings have made it possible to establish a relationship between the cellular sensory capacity and the activation of the polymodal transient receptor potential vanilloid 1 (TRPV1), which is responsible for the nociceptive response and whose desensitization could cause analgesia. Thus, the objective of this study was to determine the expression, localization, and functional activity of TRPV1 in human odontoblasts-like-cells (hOLCs) and the effect of eugenol (EUG) on its activation and desensitization. Human dental pulp stem cells (hDPSCs) were obtained from third molars and were characterized using flow cytometry, and their differentiation potential toward the osteoblastic, chondrogenic, and adipogenic lineages was investigated. Subsequently, the hDPSCs underwent odontogenic differentiation for 7, 14, and 21 days, and their phenotype (odontogenic markers dentin matrix protein-1 (DMP-1) and dentin sialoprotein (DSP)) was evaluated using immunofluorescence. The TRPV1 gene expression in hOLCs was estimated using RT-qPCR, and its localization was analyzed using immunofluorescence. Half-maximal effective concentration (EC50) from both eugenol (EUG) and capsaicin (CAP) was determined; in addition, receptor activation was evaluated against chemical, thermal, and pH stimuli. For the statistical analysis, a one-way ANOVA with a Tukey post hoc test (p<0.05) was used. After establishing the in vitro model of hOLCs and the membrane location of TRPV1, its chemical activation with EUG and CAP was demonstrated, as well as its thermal activation at ≥ 43°C and with an acidic (<6) or basic pH (between 9 and 12). Receptor desensitization was achieved after 20 min of exposure to two concentrations of EUG (603.5 and 1000 µM). These findings represent a stepping-stone for the construction of a pulp pain study model oriented toward a therapeutic alternative for the treatment of dentinal hypersensitivity.